Cl-amidine confers organ protection and improves survival in hemorrhagic shock rats via the PAD4-CitH3-NETs axis. - Huiting Yun; Yunfei Chi; Bin Wei; Hailiang Bai; Weihua Cao; Zheng Zhang; Yufang Zhang; Quanxi Zhang; Hongjie Duan (PLoS ONE, 2025)
Background The occurrence of multi-organ dysfunction following hemorrhagic shock (HS) remains a critical clinical challenge. The excessive formation of neutrophil extracellular trap (NET) Has been identified as a pivotal pathogenic mechanism. This study preliminarily elucidated the protective mechanism of the PAD4 inhibitor Cl-amidine in a rat model of HS. Methods Male Sprague-Dawley rats were subjected to sublethal (40% blood loss, n = 8) or lethal (50% blood loss, n = 10) HS. Rats were divided into Sham group (catheter placement only), HS group (catheter placement followed by blood withdrawal), Vehicle group (0.9% saline), and Cl-amidine (10 mg/kg in 0.9% saline) groups. Results Cl-amidine significantly improved the 72-h survival rate and delayed mortality in lethal HS. In Sublethal HS, the drug corrected metabolic disturbances, such as reduced lactate accumulation, while maintaining mean arterial pressure. Mechanistically, the effects of Cl-amidine included reducing circulating cell-free DNA (cf-DNA) and tissue citrullinated histone H3 (CitH3) levels, suppressing PAD4 expression, and improving histopathological outcomes (reduced edema and restored intestinal barrier integrity by upregulation of tight junction proteins Claudin-1/ZO-1). Moreover, Cl-amidine inhibited neutrophil infiltration through ICAM-1 downregulation and reduced the production of TNF-α and IL-6. Conclusions In conclusion, Cl-amidine protects against HS by targeting the PAD4-CitH3-NETs axis, breaking the vicious cycle of "NETs-inflammation", restoring barrier integrity, and alleviating multi-organ damage. The synergistic downregulation of ICAM-1 further enhances the therapeutic efficacy, highlighting Cl-amidine as a novel NETs-modulating strategy for HS. This study provides a theoretical and therapeutic foundation for the prevention and treatment of multi-organ injury following HS.